1982
DOI: 10.1159/000465404
|View full text |Cite
|
Sign up to set email alerts
|

Human IgG Allotypes Co-Occurring in More than One IgG Subclass

Abstract: Inheritance of an excess of immunoglobulin allotypes in one haplotype was encountered which could not be explained by the assumption of a duplicated locus. The surplus of allotypes was related to markers on the CH3 domain of y3 chains. Two such cases were investigated extensively. The IgG3 molecules were isolated by gel filtration and by absorption on protein A. Only the usual combination of allotypes appeared to be present on the IgG3 molecules. The supernumerary markers were found in one case on IgG2 molecul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

1985
1985
2022
2022

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 10 publications
2
16
0
Order By: Relevance
“…All the plasma were tested for G1m (1,2,3,17), G2m (23), G3m (5,6,10,11,13,14,15,16,21,24) and Gm (28) immunoglobulin allotypic markers by using a classical haemagglutination inhibition method [36]. The reagents used are described by Dugoujon et al [37] and Giraldo et al [38].…”
Section: Gm Immunoglobulin Allotypesmentioning
confidence: 99%
See 2 more Smart Citations
“…All the plasma were tested for G1m (1,2,3,17), G2m (23), G3m (5,6,10,11,13,14,15,16,21,24) and Gm (28) immunoglobulin allotypic markers by using a classical haemagglutination inhibition method [36]. The reagents used are described by Dugoujon et al [37] and Giraldo et al [38].…”
Section: Gm Immunoglobulin Allotypesmentioning
confidence: 99%
“…The notation ".." indicates that the sample was tested for G2m (23) but found to be negative for this allotype, and 5 * stands for 5, 10, 11, 13, 14. Gm (28) is presented separately from the other polymorphisms because it has been shown that it is not necessarily located on the gamma 3 chain in African populations [24].…”
Section: Gm Immunoglobulin Allotypesmentioning
confidence: 99%
See 1 more Smart Citation
“…Blood samples (20)(21)(22)(23)(24)(25) Hybridizations were carried out at 42 "C overnight in 5 x SSPE (5 x saline sodium phosphate EDTA; 0.9 M NaC1, 50 mM NaH2P04, pH 7.4, 5 mM EDTA, pH 7.4), 50% formamide supplemented with 0.5% SDS, 0.2% Ficoll 400, 0.2% bovine serum albumin (BSA), 0.2% polyvinylpyrrolidone, 5% dextran sulfate, 50 pg/ml sonicated, denatured salmon sperm DNA, and 10 ng/ml of the labeled, heat-denatured probe. The probes were labeled with 32P-dCTP by nick translation [22] at a specific activity of 0.5 x lo8-1 x lo8 cpmlpg.…”
Section: Samplesmentioning
confidence: 99%
“…Converted yl and 72 genes with y3 sequences A few years ago, we demonstrated the occurrence of some human Gm allotypes in more than one subclass [24,32]: the Gm (g5 and v) antigenic determinants, usually located on the CH3 domain of y3 chains (33-351 ( fig.l), were found on 71 chains encoded by an unusual GZrna~gS*v*z yl gene.…”
Section: Occurrence Of Igg3 Allotypes In Iggi Andmentioning
confidence: 98%